Adenotonsillectomy for Obstructive Sleep Apnea in Children with Complex Chronic Conditions. (12th December 2017) - Amin, Reshma; Holler, Theresa; Narang, Indra; Cushing, Sharon L.; Propst, Evan J.; Al‐Saleh, Suhail
Abstract : Objective: To estimate the prevalence of persistent obstructive sleep apnea postadenotonsillectomy in children with complex chronic conditions. Study Design: A retrospective cohort study. Setting: The Hospital for Sick Children Sleep laboratory. Subjects: Children ≤18 years of age who had moderate to severe obstructive sleep apnea and had polysomnography pre‐ and postadenotonsillectomy. Methods: Medical and polysomnographic data were reviewed. The prevalence of persistent obstructive sleep apnea postadenotonsillectomy was determined for the following groups: no complex chronic conditions, single‐system complex chronic conditions, and multisystem complex chronic conditions. Results: We reviewed data of 133 (84 male) children. Their mean (standard deviation) age was 5.5 (3.8) years. The persistent obstructive sleep apnea rate postadenotonsillectomy was highest in children with multisystem complex chronic conditions (57%), intermediate in children with single‐system complex chronic conditions (29%), and lowest in children without complex chronic conditions (15%), P =. 0004. The odds (confidence interval) of having persistent obstructive sleep apnea postadenotonsillectomy was 7.42 (2.16‐25.51) times higher in children with multisystem complex chronic conditions vs no complex chronic conditions and 3.35 (1.16‐9.64) times higher in children with multisystem complex chronic conditions vs single‐system complex chronic conditions. Conclusions: Although adenotonsillectomy is considered first‐line therapy in healthy children older than 2 years for the treatment of obstructive sleep apnea, there is a significantly greater risk of persistent obstructive sleep apnea postadenotonsillectomy in children with complex chronic conditions. Therefore, other surgical procedures or nonsurgical management may need to be considered as first‐line treatment for this cohort.